Investigation of surface micro-crack growth behavior of asphalt mortar based on the designed innovative mesoscopic test. (5th January 2020) - Ding, Xunhao; Ma, Tao; Gu, Linhao; Zhang, Yao
Abstract: The objective of this study is to design an innovative mesoscopic test for characterizing the damage evolutions and fracture performances of the asphalt mortar. Based on the SEM-Servopulser devices and improved specimens, the pure mode I cracking tests were conducted successfully under scanning electron microscope (SEM). It can have a real-time online observations and records of the surface micro-crack behaviors and evolutions under different loads. And it is the first time in road engineering to capture the dynamic micro-behavior and micro-structure of the bituminous materials in such high accuracy ( μm level), especially the synchronous recording when applying loads without stopping on-going tests. This proposed method will have significant meaning in revealing the fracture mechanism of the bituminous materials since the traditional specimen sizes and the self-healing property of the asphalt hinder the further micro-scale investigations in this field. With the help of the pioneering designed tests, the damage variable based on the micro-crack density was proposed and was verified by the experimental results. It is found that the interface failure dominated during the overall process in pure mode I cracking tests, which should be paid more attention on in the future material design. Graphical abstract: Image 1 Highlights: Synchronous online detection of micro-cracks in mixture was achieved by designed test. Adhesive failure rather than cohesive failure dominated during mixture cracking. Linear relationship between micro-crack density and fracture energy was verified. Surface micro-crack area could account for 70%around crack tip before its propagation.